The roles of IGF2 and DNMT methylation and elongase6 related fatty acids in metabolic syndrome. Issue 20 (22nd September 2021) - Li, Xiang; Lyu, Chen; Luo, ZhongCheng; Zhao, Jing; Wang, Zhongli; Yang, Chun; Dai, Qi; Li, Hui; Zhou, Yunhua; Li, Zi; Chen, Fuxue; Gao, Ying
Abstract : Methylation levels in IGF2 and DNMT3a genes may affect the risk of metabolic syndrome (MetS) in an ELOVL6 activity dependent way. Abstract : Background : The prevalence of metabolic syndrome (MetS) has increased along with rapid socio-economic development in China in recent decades, aggravating the burden of the health care system. Both plasma levels of fatty acids (FAs) and aberrant DNA methylation profiles are associated with MetS risk. However, studies exploring the role of DNA methylation and FAs simultaneously in MetS etiology are sparse. Objective : We aimed to explore the association between the gene methylation levels of insulin-like growth factor II ( IGF2 ), H19, DNA methyltransferases 1 ( DNMT1 ), DNA methyltransferases 3a ( DNMT3a ), and DNA methyltransferases 3b ( DNMT3b ) and MetS risk, and the etiological role of elongation of very-long-chain fatty acid elongase 6 (ELOVL6) related fatty acids. Method : Plasma levels of FAs were measured using a Gas Chromatography-Flame Ionization Detector (GC-FID) after organic extraction, and gene methylation was quantified using a real-time Quantitative Polymerase Chain Reaction (Q-PCR) detecting system after bisulfite treatment. The C18/C16 ratio was used as the indicator of ELOVL6 activity. Odds Ratio (OR) and 95% Confidence Interval (CI) were estimated with logistic regression. Results : Methylation levels in IGF2 and DNMT3a were not significantly associated with MetS risk. However, when stratified by C18/C16 ratio (high vs. low), positive associations were observed between the risk of MetS and methylation levels (>median) of IGF2a3 (OR = 3.1, 95% CI = 1.3–7.5) and DNMT3a (OR = 2.5, 95% CI = 1.1–5.8) genes, in individuals with lower C18/C16 ratios, while no significant associations were observed in subjects with high C18/C16 ratios. Conclusion : Methylation levels in IGF2 and DNMT3a genes may affect the risk of MetS in an ELOVL6 activity-dependent way among Chinese adults. Further studies in other populations are needed to validate this finding.